In situ measurement of cutting edge temperature in turning using a near-infrared fiber-optic two-color pyrometer. (May 2020) - Han, Jinghui; Cao, Kaiwei; Xiao, Lian; Tan, Xianhua; Li, Tianxiang; Xu, Long; Tang, Zirong; Liao, Guanglan; Shi, Tielin
Highlights: A near-infrared fiber-optic two-color pyrometer system to monitor the cutting edge temperature. Good stability and fast dynamic responses are validated by continuous and interrupted cutting experiments. The ability of sensing cutting regime changes during machining is validated. The relationship between the cutting temperature change and tool wear is discussed. Tool damage warning potential before the tool breakage is confirmed. Abstract: Cutting temperature in machining process has received extensive attention due to its significant influence on tool life and workpiece quality. Research on real-time monitoring of the cutting temperature still faces many challenges, including rapidly changing temperature, high temperature gradient, limited installation space, and flowing chips and coolant. In this paper, a near-infrared fiber-optic two-color pyrometer system is proposed to obtain real-time temperature of the cutting edge during turning. A sensor probe is inserted into a micro-hole of the tool near the cutting edge. The infrared rays radiated from the hole is received by the sensor probe, led by the optical fiber to a plano-convex lens, and split into two identical rays by a beam splitter. Then the two rays passing through specific band filters are focused by two plano-convex lenses on two amplified photodetectors, and the electrical signals are acquired by a data acquisition card. Typical difficult-to-cut material is selected as workpiece in turning. The pyrometer system shows good stability and dynamic response in continuous cutting and interrupted cutting experiments, respectively. The measured cutting temperature is responsive to the changed cutting regime, increasing with the increase of the cutting speed, cutting depth and feed rate in continuous cutting. Repeated cutting experiments are performed for further validation. It is found that the rapid wear in the tool flank face is accompanied by an obvious increase in the cutting temperature, and the cutting temperature rises sharply before the tool breakage. These results indicate the potential of the pyrometer for real-time monitoring of the working tool and early warning of the tool damage.